Políticas de la filosofía: migración y violencia - Magallón Anaya, Mario (Bollettino Filosofico, 2019)
This paper focuses on the impact of violence on history of humankind; on the changes, contradictions, oppositions and struggles among interests of control and the influence of a minority which seeks control. Majorities, and even some minorities, have globally exercised authority and domain on the others throughout the state and global business corporations. That’s why these minorities try to justify the contingence of violence as it was universal. Instead, the contingent violence is based on the exercise of power and domain, which becomes an attempt against people and human dignity. However, human dignity is not based on accidental or circumstantial representations, such as skin color, gender, richness, social level, etc., but on the ontological and epistemic foundation of social relationships. This problem becomes more complex with big migrations and exiles in contemporary world, from South to North. Keywords: Philosophy, Politics, Migration, Ethics, Justice